Pengembangan buku ajar microteaching bernuansa islami dalam meningkatkan pendidikan karakter mahasiswa calon guru - Efriana Jon; Ayu Permata Sari (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2019)
Students are still difficult in understanding the basic skill of teaching. There is no handbook for the students to learn independently either in the class or at home. This research was a research and development. This learning media was developed by using four-D models. From the research result conducted, it was known that the microteaching textbook with Islamic nuance in improving the character education for the prospective teacher students is at an extremely valid category. Based on limited try out, it is known that the implementation is at an extremely excellent category. The lecturer and students’ responses after using the microteaching textbook with Islamic Nuance shows positive results with the average response is practical. The result of observation on students’ activity is at extremely active category and very valid, practical, effective to be used in college